Coaches, parents, or peers: Who has the greatest influence on sports participants' life skills development?. Issue 21 (2nd November 2021) - Mossman, Gareth J.; Robertson, Colin; Williamson, Brian; Cronin, Lorcan
ABSTRACT: This study investigated the relationships between the coach, parent, and peer motivational climate and participants' life skills development in youth sport. In total, 308 participants ( M age  = 14.67, SD  = 2.20) completed a survey assessing the motivational climate (mastery and ego) and their life skills development in sport (teamwork, goal setting, social skills, emotional skills, problem solving and decision making, leadership, time management, and interpersonal communication). Multiple regression analyses found that a peer-created mastery-climate had the strongest positive associations with all eight life skills and total life skills. Coach and parent mastery-oriented climates were also positively related to five of the life skills and total life skills. A parent-created ego-climate had the strongest negative association with all life skills except for goal setting; whereas, a coach-created ego-climate was negatively related to three life skills and total life skills. Contrary to expectations, a peer-created ego-climate was positively associated with three life skills and total life skills. In practice, these novel results suggest that peers have the greatest positive influence on participants' life skills development in sport and all three social agents should be encouraged to create a mastery-climate to help promote participants' life skills development.